2019
DOI: 10.1111/aas.13448
|View full text |Cite
|
Sign up to set email alerts
|

Availability and organization of difficult airway equipment in Swedish hospitals: A national survey of anaesthesiologists

Abstract: Background: Airway complications account for almost one third of anaesthesiarelated brain damage and death. Immediate access to equipment enabling rescue airway strategies is crucial for successful management of unanticipated difficult airway situations. Methods:We conducted a nationwide survey of Swedish anaesthesiologists to analyse availability and organization of difficult airway trolleys (DATs), and multiple factors pertaining to difficult airway management, to highlight areas of potential improvement. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(75 reference statements)
0
15
0
1
Order By: Relevance
“…Recurrent training to maintain and develop preparedness and nontechnical skills is essential for successful emergency airway management 11 . Although NAP4 has led to increases in the frequency of human factors training and multidisciplinary team training, 35 national surveys commonly show low rates of airway simulation training 16,19 . Simulation‐based airway training may improve adherence to difficult airway algorithms, and increase proficiency in rarely used technical skills 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recurrent training to maintain and develop preparedness and nontechnical skills is essential for successful emergency airway management 11 . Although NAP4 has led to increases in the frequency of human factors training and multidisciplinary team training, 35 national surveys commonly show low rates of airway simulation training 16,19 . Simulation‐based airway training may improve adherence to difficult airway algorithms, and increase proficiency in rarely used technical skills 36 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, prior studies have shown deficiencies in practice of airway management techniques, 17,18 as well as lack of simulation training 19 . Less than half of Swedish anesthesiologists report undergoing team‐based difficult airway training annually 16 . Moreover, practice involving DATs is uncommon, 20 and surveys indicate that knowledge of the contents of DATs may be low 21 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…В опросе участникам предлагается ответить на вопросы, освещающие все аспекты проблемы поддержания проходимости ВДП в стационаре. Содержание опроса соответствует структуре проводимых ранее анкетных опросов врачей анестезиологов-реаниматологов РФ в рамках работы Комитета ФАР по ТДП, а также различным зарубежным исследованиям, посвященным всестороннему изучению вопросов поддержания проходимости ВДП [6,[12][13][14][15][16][17]. Анализируются профессиональный стаж, место работы и объем практической работы респондентов, их первичное образование по специальности, объем и характер полученной во время обучения базовой информации по проблеме ТДП.…”
Section: рефератunclassified